New Marketing Strategy to Increase Sales in the Digital Transformation Competition in Indonesia a Case Study of PT XYZ - Ivory Rachmalia Beskarina (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2021)
Digital transformation aims to manage an organization in light of progressing digitalization to assure sustainable value creation since it is a key to develop the new opportunity, product, and sales. PT XYZ gives data-driven solutions for business challenges helping decision-makers to build new revenue streams, to create better customer experiences, and to lower business costs. Therefore, the marketing plan is the main issue for PT XYZ to increase sales and raise awareness of the market in Indonesia. The purpose of this study is to propose a new marketing strategy for PT XYZ to compete in the digital infrastructure competition. The author would like to analyze the external and internal data using the qualitative and quantitative methods to formulate SWOT. The SWOT result used to propose new marketing strategies to increase sales and market share in Indonesia with a new STP and 7P marketing mix. In general, the impact of technological change and the right marketing strategy on PT XYZ has a positive effect because it improves human life quality and sustainable society.